1997
DOI: 10.1038/sj.bjp.0701235
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a selective 5‐HT reuptake inhibitor in combination with 5‐HT1A and 5‐HT1B receptor antagonists on extracellular 5‐HT in rat frontal cortex in vivo

Abstract: 1 Selective 5-hydroxytryptamine (5-HT; serotonin) reuptake inhibitors (SSRIs) cause a greater increase in extracellular 5-HT in the forebrain when the somatodendritic 5-HT 1A autoreceptor is blocked. Here, we investigated whether blockade of the terminal 5-HT 1B autoreceptor in¯uences a selective 5-HT reuptake inhibitor in the same way, and whether there is an additional e ect of blocking both the 5-HT 1A and 5-HT 1B autoreceptors. 2 Extracellular 5-HT was measured in frontal cortex of the anaesthetized rat by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
79
0
2

Year Published

1999
1999
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(90 citation statements)
references
References 27 publications
9
79
0
2
Order By: Relevance
“…However, a small or no increase in 5-HT has been measured using microdialysis following acute SSRI administration (Sharp et al, 1997;Roberts et al, 1999;Dawson and Nguyen, 2000) questioning whether the acute anxiolytic effects are due to changes in 5-HT levels or whether other neurotransmitter systems play a role. It could be postulated that an overflow technique such as microdialysis simply lacks the sensitivity to measure small changes in 5-HT, and increases in synaptic 5-HT are sufficient to mediate the observed acute anxiolytic effect.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a small or no increase in 5-HT has been measured using microdialysis following acute SSRI administration (Sharp et al, 1997;Roberts et al, 1999;Dawson and Nguyen, 2000) questioning whether the acute anxiolytic effects are due to changes in 5-HT levels or whether other neurotransmitter systems play a role. It could be postulated that an overflow technique such as microdialysis simply lacks the sensitivity to measure small changes in 5-HT, and increases in synaptic 5-HT are sufficient to mediate the observed acute anxiolytic effect.…”
Section: Discussionmentioning
confidence: 99%
“…Preclinical microdialysis studies have demonstrated that the selective 5-HT 1B receptor antagonist SB-224289 augments the 5-HT increase seen with paroxetine, and that WAY100635 further potentiates this effect (Roberts et al, 1999). Another 5-HT 1B/D receptor antagonist, GR127935, also augments an SSRI effect in microdialysis (Rollema et al, 1996;Gobert et al, 1997) and potentiates the effects of an SSRI/5-HT 1A receptor antagonist combination (Sharp et al, 1997;Dawson and Nguyen, 2000). Therefore, 5-HT 1A/B/D receptor antagonism may play a beneficial role in the augmentation of the effects of SSRIs.…”
Section: Introductionmentioning
confidence: 99%
“…Given that in functional assays (-)pindolol acts as an antagonist at the latter receptor (Schoeffter and Hoyer 1989), it is plausible that the latter property could account, at least in part, for the potentiating effect of (-)pindolol on the suppressant effect of venlafaxine on the firing activity of hippocampal neurons that was observed in the present study. Nonetheless, while in vivo microdialysis studies suggest that a 5-HT 1B antagonism may increase the output of 5-HT elicited by 5-HT reuptake inhibitors, there is evidence that this would only be so in the presence of normal firing of 5-HT neurons, i.e., in the presence of an adequate 5-HT 1A autoreceptor blockade (Hjorth 1993;Sharp et al 1997). The 5-HT 1A antagonism of (-)pindolol, thus, appears to be a sine qua non condition for its 5-HT 1B antagonistic property to be of functional relevance.…”
Section: Discussionmentioning
confidence: 99%
“…Since SSRIs produce a tonic elevation of serotonin levels in the extracellular space (Fuller, 1994;Malagié et al, 1995), their therapeutic effect is probably mediated, at least in part, by action at various levels of the serotonergic system, notably at serotonergic receptors (Barnes and Sharp, 1999). In particular, it has been proposed that the antidepressant effects of SSRIs would be related to desensitization of somatodendritic 5-HT 1A and terminal 5-HT 1B autoreceptors (Blier et al, 1987;Artigas et al, 1994Artigas et al, , 2001Pineyro and Blier, 1999), which is induced by and participates indirectly in the increase in 5-HT concentration in the extracellular space (Gartside et al, 1995(Gartside et al, , 1999Sharp et al, 1997;Trillat et al, 1998;Adell et al, 2001;Malagié et al, 2001).…”
Section: Introductionmentioning
confidence: 99%